2000
DOI: 10.1080/02724930092110
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis in sickle cell haemoglobinopathy with elevated fetal haemoglobin

Abstract: The prevalence rate and characteristics of osteomyelitis in children below 15 years of age were studied in a population characterized by a high prevalence of sickle cell disease (SCD) with elevated fetal haemoglobin (HbF). All children born in our institution routinely undergo a haemoglobinopathy screening test. Osteomyelitis developed in 25 children (16 boys and nine girls) with a mean age of 5.5 years. Fourteen had sickle cell disease (SCD) and 11 had no haemoglobinopathy. The prevalence of osteomyelitis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The remaining 258 abstracts were reviewed for inclusion and exclusion criteria, 30 articles were examined in full and 18 included in quantitative analysis. 12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The 12 articles that were excluded after being examined in full did not clearly or failed to differentiate between the homozygous and heterozygous disease or were case reports.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 258 abstracts were reviewed for inclusion and exclusion criteria, 30 articles were examined in full and 18 included in quantitative analysis. 12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The 12 articles that were excluded after being examined in full did not clearly or failed to differentiate between the homozygous and heterozygous disease or were case reports.…”
Section: Study Selectionmentioning
confidence: 99%
“…There were no reported randomized control trials, metaanalyses or prospective studies found in the literature reporting on the rates of osteomyelitis in SCA. There were 14 retrospective studies 17,[19][20][21][22][23][24][25][27][28][29][30][31][32] and 4 case series studies 18,24,26,33 included in analysis. Two studies included analysis of heterozygote or SCT patients, however, distinguished clearly between homozygote and heterozygote patients.…”
Section: Study Characteristicsmentioning
confidence: 99%